2018
DOI: 10.1161/atvbaha.117.309918
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell–Derived Von Willebrand Factor, But Not Platelet-Derived, Promotes Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: EC-VWF, but not Plt-VWF, contributes to VWF-dependent atherosclerosis by promoting platelet adhesion and vascular inflammation. Plt-VWF even in the absence of a disintegrin and metalloprotease with thrombospondin type I repeats-13, both in platelet and plasma, was not sufficient to promote atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…This raises the question of whether dysregulated endothelial chemokine release as a result of VWF deficiency may also affect atherogenesis. Several studies in murine models have indeed shown that VWF‐deficient mice are protected from experimental atherosclerosis . However, firm evidence for a similar protective effect in patients with VWD has so far not been found (reviewed in).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of whether dysregulated endothelial chemokine release as a result of VWF deficiency may also affect atherogenesis. Several studies in murine models have indeed shown that VWF‐deficient mice are protected from experimental atherosclerosis . However, firm evidence for a similar protective effect in patients with VWD has so far not been found (reviewed in).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in murine models have indeed shown that VWF-deficient mice are protected from experimental atherosclerosis. [59][60][61] However, firm evidence for a similar protective effect in patients with VWD has so far not been found (reviewed in 62 ). In vitro IL-6 and IL-8 constitutive secretion did not show large differences between CTRL and VWF −/− BOECs ( Figure 5), which is consistent with previous observations that the bulk of newly synthesized IL-6 and IL-8 does not enter WPBs but is released via the constitutive secretion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is often assumed that only activated platelets bind leukocytes, recent studies have revealed that platelets captured under flow by VWF released from activated endothelial cells can recruit leukocytes (Doddapattar et al, 2018;Zheng et al, 2015). If VWF-GPIbα-dependent signaling is capable of promoting leukocyte binding, this may be highly relevant to the non-hemostatic platelet functions (particularly when other agonists are not available/abundant), but may also provide major mechanistic insights into the early recruitment of leukocytes during the initiation of DVT.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo molecular imaging has recently been used to confirm histological findings that arterial platelet adhesion in atherosclerosis is mediated by increased endothelial-associated von Willebrand factor (vWF) and exposure of the vWF A1 binding domain for the glycoprotein-Ibα (GPIbα) subunit of the platelet GPIb-IX-V complex ( 10 , 11 , 12 ). Accumulation of self-associated vWF on the endothelium in atherosclerosis has been attributed in part to impaired cleavage by ADAMTS-13 ( 12 , 13 , 14 ).…”
mentioning
confidence: 99%